Plant Pathogen Life-History Traits and Adaptation to Environmental Constraints - Le May, Christophe; Montarry, Josselin; Morris, Cindy E.; Frenkel, Omer; Ravigné, Virginie (Frontiers Media SA, 2020)
Parasites exhibit a range of life-history strategies that influence spatial and temporal disease dynamics, epidemiology development and, through this, the genetic diversity and spatial structure of their populations, and the evolutionary dynamics within populations. Parasites exhibit a range of life-history traits, including different life-cycle complexity, dispersal and survival strategies, transmission modes, and dispersal ability. These are important determinants of the frequency and predictability of interactions with host species. These determinants are also involved in the ability of parasites to adapt to varying ecological factors including changes in the abiotic environment, evolution of agrosystem characteristics, and direct or indirect competition with other co-occurrence parasites species. The aim of this Research Topic is to collect studies on plant pathogen life history traits and adaptation to environmental constraints.